Antimicrobial properties of a new polymeric material based on poly(2-hydroxyethyl methacrylate) - Chornopyshchuk, Roman; Nagaichuk, Vasyl; Gerashchenko, Igor; Nazarchuk, Halyna; Kukolevska, Olena; Chornopyshchuk, Nataliia; Sidorenko, Svetlana (Acta Biomedica Atenei Parmensis, 2022)
Background and aim. Оne of the promising areas is the development of synthetic wound dressings with programmed release of active substances that can affect various elements in the pathogenesis of the wound process. The aim was to study the antimicrobial properties of a new polymeric material based on poly(2-hydroxyethyl methacrylate).Methods: 2-hydroxyethyl methacrylate, dimethacrylate triethylene glycol as crosslinking agent, polymerization initiator of azobisizobutyronitrile along with a porogen and one of the antimicrobial agents, including decamethoxin, chlorhexidine bigluconate, silver nitrate, octenidine, furacilin, metronidazole, dioxidine, and gentamicin were used to synthesize a new material with antimicrobial activity. For comparison, polymer samples synthesized without adding antimicrobials were used, as well as known dressing materials: carbon material, porcine skin, which were immersed into 0.02% decamethoxin solution before use, as well as silver-containing dressing, hydrogel dressings, including those filled with silver. Determination of antibacterial properties was performed by diffusionmethod.Results. Low antimicrobial activity of the studied existing wound dressings, which are widely used in medical practice, even under conditions of their saturation with antiseptic substances, has been established. Samples of the suggested polymeric material with the addition of antimicrobial substances showed the ability to inhibit the growth of the test strains of microorganisms at a sufficient level, especially with such fillers as decamethoxin, gentamicin, dioxidine. When metronidazole was added to the polymeric material, a reliable antimicrobial effect on the anaerobic microorganisms was established.Conclusions.Modification of the polymeric material of poly(2-hydroxyethyl methacrylate) by adding antimicrobial substances allows to ensure its high antimicrobial properties against different microorganisms.